Myosin XVA isoforms participate in the mechanotransduction-dependent remodeling of the actin cytoskeleton in auditory stereocilia - López-Porras, Ana I.; Kruse, Ava M.; McClendon, Mark T.; Vélez-Ortega, A. Catalina (Frontiers in Neurology, 2024)
Auditory hair cells form precise and sensitive staircase-like actin protrusions known as stereocilia. These specialized microvilli detect deflections induced by sound through the activation of mechano-electrical transduction (MET) channels located at their tips. At rest, a small MET channel current results in a constant calcium influx which regulates the morphology of the actin cytoskeleton in the shorter ‘transducing’ stereocilia. However, the molecular mechanisms involved in this novel type of activity-driven plasticity in the stereocilium cytoskeleton are currently unknown. Here, we tested the contribution of myosin XVA (MYO15A) isoforms, given their known roles in the regulation of stereocilia dimensions during hair bundle development and the maintenance of transducing stereocilia in mature hair cells. We used electron microscopy to evaluate morphological changes in the cytoskeleton of auditory hair cell stereocilia after the pharmacological blockage of resting MET currents in cochlear explants from mice that lacked one or all isoforms of MYO15A. Hair cells lacking functional MYO15A isoforms did not exhibit MET-dependent remodeling in their stereocilia cytoskeleton. In contrast, hair cells lacking only the long isoform of MYO15A exhibited increased MET-dependent stereocilia remodeling, including remodeling in stereocilia from the tallest ‘non-transducing’ row of the bundle. We conclude that MYO15A isoforms both enable and fine-tune the MET-dependent remodeling of the actin cytoskeleton in transducing stereocilia, while also contributing to the stability of the tallest row.